Pengaruh Sistem Pembayaran COD (Cash On Delivery) Terhadap Minat Belanja Online di Platform E-commerce Shopee Pada Mahasiswa UIN Sultan Maulana Hasanuddin Banten - Uldiana Sari; Syahrul Faizin; Elsa Agustiani; Zaini Ibrahim; Wahyu Hidayat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Nowadays we can shop online through e-commerce platforms, which makes the time to shop more effective and efficient. Because it can be done anytime and anywhere even just from home. There are several payment systems that can be done when shopping online on an e-commerce platform, one of which is the COD (Cash On Delivery) payment system. The purpose of this study is to determine the effect of the COD (Cash On Delivery) payment system on online shopping interest in the Shoope e-commerce platform, especially for UIN Sultan Maulana Hasanudin Banten students. The instrument used for data collection in this study was a survey with a questionnaire consisting of 48 respondents. The research sample is students of UIN Sultan Maulana Hasanudin Banten who actively use the Shoope e-commerce platform. Data analysis was carried out using simple linear regression techniques. From the results of this study, the cash on delivery payment system has a positive influence on shopping interest on the shoope e-commerce platform with a significance level of 0.000 in the simple linear regression data analysis test.